A study on the relationship between spending patterns and saving habits among Universiti Malaysia Kelantan (UMK) students in Campus Kota - Ee Siang Ling; Intan Farihah Matali; Nur Shahida Izzati Mohd Zulhadi; Sofya Nabihah Roslan (2024)
This study looks into how Universiti Malaysia Kelantan (UMK) students' financial well-being is affected by their current spending and saving behaviours. Young adults, especially those pursuing higher education, need to be financially literate and have good money management skills because they frequently encounter special financial possibilities and obstacles. The study uses a method approach which is surveys, to evaluate UMK students' spending and saving habits. The results show that there is a broad variation in the saving and spending behaviours of UMK students. Many students show a tendency to spend their money on things that are not necessary, and a sizable percentage of them also practice prudent saving. The study investigates the variables that affect these financial behaviours, such as spending patterns, sources of income, type of expenses, and purchase influence. Comprehending the financial practices of UMK students is crucial for both their individual financial welfare and the creation of efficient financial literacy initiatives and guidelines. The findings of this study add to a larger conversation about university students' resilience and financial readiness, with possible ramifications for enhancing financial literacy and promoting responsible spending and saving practices in young adults.